2010
DOI: 10.1016/j.neulet.2010.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and omega-6 fatty acids suppress ER- and oxidative stress in cultured neurons and neuronal progenitor cells from mice lacking PPT1

Abstract: Reactive oxygen species (ROS) damage to brain lipids, carbohydrates, proteins, and DNA may contribute to neurodegeneration. We previously reported that ER-and oxidative stress cause neuronal apoptosis in infantile neuronal ceroid lipofuscinosis (INCL), a lethal neurodegenerative storage disease, caused by palmitoyl-protein thioesterase-1(PPT1)-deficiency. Polyunsaturated fatty acids (PUFA) are essential components of cell membrane phospholipids in the brain and excessive ROS may cause oxidative damage PUFA lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…For example, increased incorporation of the saturated fatty acid, palmitate, into ER lipids induces ER stress in cells [38]. In contrast, polyunsaturated fatty acids suppress ER stress [39]. Our data show that even in chow-fed mice, the lack of PEMT reduces the molar ratio of PC/PE in hepatic ER coincident with the induction of ER stress, but does not increase hepatic TG content (Fig.…”
Section: Aberrant Er Phospholipid Composition Is Associated With Er Smentioning
confidence: 58%
“…For example, increased incorporation of the saturated fatty acid, palmitate, into ER lipids induces ER stress in cells [38]. In contrast, polyunsaturated fatty acids suppress ER stress [39]. Our data show that even in chow-fed mice, the lack of PEMT reduces the molar ratio of PC/PE in hepatic ER coincident with the induction of ER stress, but does not increase hepatic TG content (Fig.…”
Section: Aberrant Er Phospholipid Composition Is Associated With Er Smentioning
confidence: 58%
“…Hussein and coworkers [25] also found an increase in NO• production associated with a reduction of the arterial blood pressure in spontaneously hypertensive rats, suggesting an antihypertensive role of ASTA. Recently, Kim and colleagues [67] found that ASTA reduced the activation of the transcription factor NF-κB and decreased the IL-6 production in microglial cells. Since NFκB is the most important pathway in immune cells, responsible of inducing NO• production by inducing iNOS expression, we can speculate that ASTA can promote a NF-κB activation which leads to an increase in NO• production.…”
Section: Discussionmentioning
confidence: 98%
“…The fact that the number of unsaturations is relevant for the protective effect supports the idea that direct reaction of PUFAs with ROS underlies the protective mechanism. However, indirect protective pathways cannot be ruled out because PUFAs are involved in complex intracellular signaling in the nervous system, promoting neuroprotection through modulation of inflammatory responses (43,44).…”
Section: Discussionmentioning
confidence: 99%